Cumulative industrial noise impact on the environment - WSZOŁEK, Tadeusz (Archives of Acoustics, 2017)
The paper presents basic legal conditions, applicable to the calculation of cumulative noise levels in the environment with indication mainly on lack of detailed regulations both in formal and methodological approach for evaluating those levels. The paper is focused on methodological approach with the emphasis on analysis of existing case studies in the industry. The main subject of the analysis is the cumulationof industrial noise sources: newly designed and existing ones, together with a proposal of accumulate other types of the noise. Evaluation of cumulative noise levels for new (designed) objects is realised by computational methods, and for existing objects, by measurements or by combination of measurement and computational methods. It is assumed that the cumulative level is an energetic sum of the ratinglevels for all installations and it will not exceed the limit value in a given place. For the cumulation of different noise sources, the weighting for criterion values of these sources will be applied in aggregation.